Glasgow 2014, the media and Scottish politics: The (post)imperial symbolism of the Commonwealth Games. (May 2018) - Whigham, Stuart; Black, Jack
This article critically examines print media discourses regarding the 2014 Glasgow Commonwealth Games. The forthcoming analysis examines the political symbolism of the Commonwealth Games with regard to the interlinkages between the British Empire, sport and the global political status of the United Kingdom. The article gives specific consideration to the United Kingdom's declining global power as well as the interconnections between the 2014 Games and the Scottish independence referendum. Hechter's 'internal colonialism' thesis, which portrays Scotland's marginalised status within the United Kingdom, is drawn upon to critically explore the political symbolism of sport for Scottish nationalism. Discussion then focuses upon the extent to which the modern Commonwealth is symptomatic of the United Kingdom's declining status as a global power. Finally, the existence of these narrative tropes in print media coverage of the Commonwealth Games is examined, allowing for critical reflections on the continuing interconnections between the media, sport, nationalism and post-imperial global politics.